(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Now-a-days, the banking industry is operating in an environment that has become much difficult due to increased competition fast technological changes and growth of alternative banking institutions. For achieving success in the banking industry and to satisfy the customers, they must satisfy workforce as a source of competitive advantage. The objective of the present study is to examine the impact of demographic characteristics (age, gender, Income, Education and designation) on performance of employees of Chhattisgarh Rajya Gramin Bank.